Releitura ilustrada de poemas de Lau Siqueira - Santos, Liziane Bomfim dos (2025)
This work presents an interdisciplinary approach to poems by Lau Siqueira, aimed at improving literary reading of poems in the classroom. In this sense, it proposes the re-reading, through illustration activities, of poems by contemporary writer Lau Siqueira, with a focus on poems that address social issues, since they allow important reflections to develop the student's critical sense. Based on Pinheiro’s (2000, 2018) perspective of teaching the poem in the classroom and Cosson’s (2009) stages of reading, this work is also based on Rouxel’s (2012) subjectivity and perspective of the empirical subject, as well as dialog with the Plastic Arts. The product is a pedagogical notebook which, on the one hand, presents considerations and guidelines for teachers on working with the lyric genre in the classroom, and, on the other, details the methodology used for the proposed rereading. It is hoped that this production will help to train competent and engaged readers, promoting the visibility of poetry in the pedagogical context.